Integrating a palliative approach in a transcatheter heart valve program: Bridging innovations in the management of severe aortic stenosis and best end-of-life practice. (1st April 2014) - Årestedt, Kristofer; Beattie, James M; Lauck, Sandra; Garland, Ella; Achtem, Leslie; Forman, Jacqueline; Baumbusch, Jennifer; Boone, Robert; Cheung, Anson; Ye, Jian; Wood, David A; Webb, John G
Abstract: Severe aortic stenosis (AS) is the most prevalent structural heart disease and affects primarily older adults in their last decade of life. If the risk for surgery is high, transcatheter aortic valve implantation (TAVI) is the treatment of choice for many patients with suitable anatomy who are likely to derive significant benefit from this innovative and minimally invasive approach. In a large transcatheter heart valve (THV) centre that offers TAVI as one of the treatment options, of 565 consecutive referrals for the assessment of eligibility for TAVI over 18 months, 78 (14%) were deemed unsuitable candidates for TAVI or higher risk surgery by the interdisciplinary Heart Team because of their advanced disease, excessive frailty or comorbid burden. Concerns were raised for patients for whom TAVI is not an option. The integration of a palliative approach in a THV program offers opportunities to adopt best end-of-life practices while promoting innovative approaches for treatment. An integrated palliative approach to care focuses on meeting a patient's full range of physical, psychosocial and spiritual needs at all stages of a life-limiting illness, and is well suited for the severe AS and TAVI population. A series of interventions that reflect best practices and current evidence were adopted in collaboration with the Palliative Care Team and are currently under evaluation in a large TAVI centre. Changes include the introduction of a palliative approach in patient assessment and education, the measurement of symptoms, improved clarity about responsibility for communication and follow-up, and triggering referrals to palliative care services.